The gastric microbiome altered by A4GNT deficiency in mice - Gong, Dawei; Gao, Yuqiang; Shi, Rui; Xu, Xiaona; Yu, Mengchao; Zhang, Shumin; Wang, Lili; Dong, Quanjiang (Frontiers in Microbiology, 2025)
BackgroundSelective antimicrobial effects have been found for α1,4-linked N-acetylglucosamine residues at the terminus of O-glycans attached to a core protein of gastric gland mucin. A4gnt encodes α1,4-N-acetylglucosaminyl transferase, which is responsible for the biosynthesis of α1,4-linked N-acetylglucosamine. The impact of A4GNT on the establishment and homeostasis of the gastric microbiome remains to be clarified. The aim of this study was to characterize the gastric microbiome in mice deficient for the production of α1,4-linked N-acetylglucosamine.MethodsThe gastric microbiome within A4gnt−/− mice and wild-type mice was analyzed using high-throughput sequencing of bacterial 16S rRNA.ResultsIn A4gnt−/− mice, which spontaneously develop gastric cancer, the community structure of the gastric microbiome was altered. The relative abundance of mutagenic Desulfovibrio and proinflammatory Prevotellamassilia in these mice was significantly increased, especially 4 weeks after birth. The co-occurrence network appeared to be much more complex. Functional prediction demonstrated considerable decreases in the relative frequencies of functions associated with polysaccharide metabolism and transportation.ConclusionThe distinct profile in A4gnt−/− mice demonstrated a vital role of A4GNT in the establishment of the gastric microbiome. A dysbiotic gastric microbiome may contribute to the spontaneous development of gastric cancer in mice.